The Influence of Self-Efficacy, Work Flexibility and Job Crafting on Job Satisfaction of Employees at Radio Republik Indonesia Yogyakarta: inggris - Elly Agustin, Elly Agustin; Ignatius Soni Kurniawan; Mohammad Ahyar Syafwan Lysander (Amkop Management Accounting Review (AMAR), 2025)
Study This motivated by the importance of improvement satisfaction Work employees who can influenced by various factor psychological and situational, including efficacy self, flexibility work, and job crafting. Research objectives This is For analyze influence efficacy self, flexibility work, and job crafting towards satisfaction Work employee at Radio Republik Indonesia (RRI) Yogyakarta. Research this is research quantitative with method census in determination amount respondents. Data collection was carried out through distribution questionnaire in a way direct to all over population research . The collected data furthermore processed and analyzed use device Smar-PLS software 4. Collected data furthermore processed and analyzed use device Smar-PLS 4 software with Structural Equation Modeling (SEM) approach. Research results This show that efficacy self No influential significant to satisfaction Work employees, flexibility Work influential positive and significant to satisfaction Work employees, while job crafting No influential positive and significant to satisfaction Work employee. Findings This indicates that flexibility work is a factor important things that can increase satisfaction work, while efficacy self and job crafting yet give influence directly real. Therefore​ that, organization expected can create system more work​ flexible and supportive balance between life personal and work to improve satisfaction Work employee.